Influence of magnetic field of a radial focusing external magnetically insulated diode on emission behavior of intense pulsed ion beam; Nuclear Instruments and Methods in Physics Research B; Vol. 537 - Xu Mo-Fei; Kuang Shicheng; Xiang Yu; Zhang Shijian; Yan Sha; Remnev (Remnyov) G. E. Gennady Efimovich; Le Xiaoyun (2023, 2023)
Title screen